Pengetahuan yang Bias Nilai dalam Proses Pengarsipan Film: Studi Kasus Atas Karya Ratna Asmara: Value-Biased Knowledge in the Film Archiving Process: A Case Study of Ratna Asmara's Work - Robby Dwiki; LG. Saraswati Putri (Jurnal Filsafat Indonesia, 2026)
Film is not only function as artistic expression of human condition, but also plays a crucial role in shaping knowledge and collective memory. However, the discourse of Indonesian cinema is dominated by masculine narratives, reflected in the disappearance of the name of its first female director, Ratna Asmara. The absence of Ratna Asmara's name is a tangible form of the value-laden biases operating within film archiving. This article aims to examine film archiving as a non-neutral mechanism of knowledge production, focusing on gender disparity. Employing a feminist perspective in archival studies, this research analyzes the absence of information and limited access to Ratna Asmara's films and utilizes Sandra Harding's standpoint theory and Helen Longino's contextual empiricism to explore the collective actions of knowledge agents, such as Umi Lestari and Kelas Liarsip. The findings of this study demonstrate that archival biases not only distort existing knowledge through a partial history but also reinforce and perpetuate existing gender inequalities. The restoration and archiving work on the film Dr. Samsi by communities and academics proves the necessity of marginalized perspectives to produce inclusive and equitable knowledge. These findings underscore the importance of critical reflection on the concealed politics of knowledge within film archiving